Analisis dan Perancangan Data Warehouse untuk Penjualan, Identifikasi Status Distributor, dan Perpanjangan Masa Aktif Distributor pada PT Harmoni Dinamik Indonesia - Gredion Prajena (Bina Nusantara University, 2013)
The purpose of this study is to analyze sales data from warehouse to distributors, identification of distributor status, and extension periods of active distributors. From the analysis, a data warehouse application is created with user interfaces that are easy to understand so as it can facilitate executive decision making. The analysis is done through the following steps: survey of the running system, analysis of the data obtained from the survey, identification of the information needed for data warehouse creation and identification requirements of the system to be built. Meanwhile, designing a data warehouse uses the Nine-Step Methodology of Ralph Kimball. The result is a data warehouse containing relevant and required information for executives to make decisions. The data warehouse application displays information to the user interface that is easy to understand and quick in making the report. The data needed by the company have been analyzed and produce useful information for executives. In addition, the reports can be generated quickly and the results of the analysis shown in the form of charts and pivot facilitate decision making more rapidly and precisely.